CASH WAQF FOR MICROFINANCE: A BIBLIOMETRIC ANALYSIS - Aini, Zahriya Nurul (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: Waqf is one of the Islamic social financial instruments, having the distinctive characteristic that waqf assets are donated voluntarily by the wakif and are permanently designated for social benefits. Waqf can be used for productive or commercial activities to generate profits by Sharia law. Cash waqf can play a role in supporting the overall development process, both in human resource development, as well as in economic and social development. This study tries to explore the role of cash waqf for microfinance which can subsequently help the people's economy. Methods: The research method used in this research is quantitative research with bibliometric analysis. Data sources collected secondary data obtained from the Google Scholar database. Data were obtained using Publish or Perish (POP) software and analyzed using VOSviewer software. Results: The results of this research show that, from data searches using the keywords